Biocompatibility of chitosan carriers with application in drug delivery - Rodrigues, Susana (2012)
Chitosan is one of the most used polysaccharides in the design of drug delivery strategies for administration of either biomacromolecules or low molecular weight drugs. For these purposes, it is frequently used as matrix forming material in both nano and micron-sized particles. In addition to its interesting physicochemical and biopharmaceutical properties, which include high mucoadhesion and a great capacity to produce drug delivery systems, ensuring the biocompatibility of the drug delivery vehicles is a highly relevant issue. Nevertheless, this subject is not addressed as frequently as desired and even though the application of chitosan carriers has been widely explored, the demonstration of systems biocompatibility is still in its infancy. In this review, addressing the biocompatibility of chitosan carriers with application in drug delivery is discussed and the methods used in vitro and in vivo, exploring the effect of different variables, are described. We further provide a discussion on the pros and cons of used methodologies, as well as on the difficulties arising from the absence of standardization of procedures.